PHOTOVOLTAIC PROPERTIES OF SILVER-DOPED NANOCRYSTALLINE CDTE–SIO₂–SI HETEROSTRUCTURES (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
This study investigates the photovoltaic properties of silver (Ag)-doped nanocrystalline CdTe–SiO₂–Si heterostructures. It was found that increasing the tilt angle of the texture axis enhances the photo-EMF, confirming a strong correlation between the crystalline structure and the optoelectronic efficiency of CdTe:Ag films.